Digitalisasi Dan Transformasi Teknologi Dalam Pengembangan Industri Halal Di Era Ekonomi Digital: Digitalisasi dan Transformasi - Apriliyani, Feni; Munajat, Ma'mur; Fatmasari, Dewi; Jaelani, Aan (STAI Al Musaddadiyah Garut, 2025)
The development of the digital economy has brought significant changes to the halal industry through digitalization and technological transformation. The use of digital technology affects not only production and distribution processes but also halal certification systems, supply chain transparency, and marketing strategies for halal products. On the one hand, this transformation creates opportunities to improve business efficiency and expand market access, particularly for halal industry players. On the other hand, it presents challenges related to human resource readiness, digital literacy, and the consistent application of ethical values and sharia compliance. This study aims to examine the role of digitalization and technological transformation in the development of the halal industry in the digital economy era. The research adopts a qualitative approach using a literature review method by analyzing academic publications, policy documents, and digital-based halal industry practices. The findings indicate that digitalization contributes positively to accelerating halal certification processes, enhancing product traceability, and expanding marketing reach through digital platforms. Technological transformation also encourages the emergence of innovative halal business models that are more adaptive to market dynamics. Nevertheless, the development of a digital-based halal industry requires responsive regulatory support, strengthened digital literacy among business actors, and the integration of sharia values to ensure that technological utilization remains sustainable and responsible. Keywords: digitalization; technological transformation; halal industry; digital economy.